Lajos Takács and his work. (1994) - Dshalalow, Jewgeni H.; Syski, Ryszard
Abstract : This paper, written in honor of the 70th birthday of Lajos Takács, addresses his life and work, and includes some personal observations and appreciation of his contributions. In particular, it includes a short biography, an informal discussion of some of his major research areas (queueing, fluctuations, waiting time processes, and random rooted trees), and an account of the relationship of his work to that of Félix Pollaczek.